Influence of water-rock interactions on the presence of dissolved radon in groundwater - De Lima, Jorge Luis Nepomuceno; Bonotto, Daniel Marcos [UNESP] (My University, 2012)
Radon (222Rn, half-life 3.84 days) is a naturally occurring volatile noble gas formed from the normal radioactive decay series of 238U, according to the following decay sequence: 238U (4.49 Ga, α) → 234Th (24.1 d, β-) → 234Pa (1.18 min, β-) → 234U (0.248 Ma, α) → 230Th (75.2 Ka, α) → 226Ra (1622 a, α) → 222Rn (3.83 d, α) → ... It is colorless, odorless, tasteless, chemically inert and radioactive gas produced continuously in rocks and soils through α-decay of 226Ra, with some atoms escaping to the surrounding fluid phase, such as groundwater and air. It is subjected to recoil at birth, with the emanated fraction relatively to that produced in the solid phase being dependent on factors such as total surface area of solids and concentration/distribution of 238U (226Ra) in the minerals. 222Rn decays to stable lead according to the sequence: 222Rn (3.83 d, α) → 218Po (3.05 min, α) → 214Pb (26.8 min, β-) → 214Bi (19.7 min, β-) → 214Po (0.16 ms, α) → 210Pb (22.3 a, β-) → 210Bi (5 d, β-) → 210Po (138.4 d, α) → 206Pb. High 222Rn concentrations occur in groundwater in many areas where wells are used for domestic water supply, inclusive in small rural water supplies. Some natural processes related to high concentration of radon in groundwater are: low transmissivity zones, uranium content of the source rock, severe chemical weathering, hydrothermal solution, deposition, extensive fracturing and variations in stress in rocks associated with seismicity. Potential health hazards from radon in consuming water have been considered worldwide, with many countries adopting the guideline activity concentration of 100 Bq/L for drinking water quality recommended by WHO. Despite the concerns coupled to the health risks due to ingestion of dissolved radon in drinking water, the Brazilian Code for Mineral Waters considered the radioactivity as an important parameter for classifying them. This legislation was established by Register 7841 published on 8 August 1945 and it considers that the waters can be classified as radioactive if they contain dissolved radon according to three different levels. This chapter reports the results of an investigation held in different aquifer systems focusing the presence of dissolved radon and its generation by variable rock matrices. The presence of this gas will be particularly focused in mineral waters occurring in Águas da Prata spa, São Paulo State, Brazil, as they are occasionally used for human consumption. © 2012 Nova Science Publishers, Inc.